Legacy System Integration in the Insurance Sector: Challenges and Solutions - Krothapalli, Bhavani; Venkatasubbu, Selvakumar; Prabhu Rambabu, Venkatesha (Journal of Science & Technology, 2021)
In the contemporary insurance sector, the integration of legacy systems presents a myriad of complex challenges that can significantly impact operational efficiency, data integrity, and overall organizational agility. Legacy systems, characterized by outdated technologies and methodologies, often coexist with modern digital infrastructures, necessitating effective integration strategies to ensure seamless data flow and functional coherence. This paper investigates the multifaceted challenges associated with integrating these legacy systems within the insurance industry and proposes a comprehensive set of solutions aimed at mitigating these challenges. The study delineates three primary categories of barriers to legacy system integration: technical, operational, and organizational. Technical challenges include issues related to data incompatibility, system interoperability, and the constraints of outdated hardware and software. These technical barriers often necessitate sophisticated data mapping, transformation, and middleware solutions to achieve effective integration. Operational barriers pertain to the complexities of aligning legacy systems with contemporary operational processes and workflows, often exacerbated by the rigidity of legacy system architectures. Furthermore, organizational challenges involve resistance to change, the necessity for re-skilling personnel, and the management of stakeholder expectations. To address these challenges, this paper proposes a range of solutions. Technically, the deployment of application programming interfaces (APIs), service-oriented architecture (SOA), and enterprise service buses (ESBs) are discussed as viable approaches to enhance system interoperability and data exchange. The use of middleware solutions and data integration platforms is advocated to bridge the gap between legacy systems and modern technologies. Operationally, the paper recommends adopting a phased integration approach, involving pilot testing and iterative implementation to minimize disruption and optimize integration outcomes. Organizationally, fostering a culture of change management, investing in training programs, and engaging stakeholders through transparent communication are essential strategies for overcoming resistance and ensuring successful integration. The paper further explores case studies and empirical evidence to illustrate the practical application of these solutions, highlighting the benefits and potential pitfalls associated with each approach. By synthesizing technical, operational, and organizational perspectives, this study aims to provide a holistic framework for addressing the challenges of legacy system integration in the insurance sector. The proposed strategies are intended to facilitate a smoother transition, ensuring that legacy systems can operate harmoniously with modern systems, thereby enhancing overall functionality and efficiency.